2015
DOI: 10.1039/c4dt02904f
|View full text |Cite
|
Sign up to set email alerts
|

p-Type mesoscopic NiO as an active interfacial layer for carbon counter electrode based perovskite solar cells

Abstract: Replacement of the ZrO2 insulator layer in the state-of-the-art TiO2/ZrO2/carbon structure by mesoscopic p-type NiO particles led to 39% increase of energy conversion efficiency of hole-conductor-free organometallic perovskite heterojunction solar cells with carbon counter electrodes. In these cells, the light absorber, CH3NH3PbI3, formed instantly inside the pores of the entire TiO2/NiO/carbon layer upon sequential deposition of PbI2 and CH3NH3I. Photoluminescence, impedance spectroscopy and transient photovo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 65 publications
1
85
0
1
Order By: Relevance
“…PCBM/Al or a carbon electrode is generally employed for electron collection. In a recent report, a layered mesoporous scaffold successively assembling both n-type TiO 2 and p-type NiO has been shown [116]. The device exhibited extended electron lifetime and improved hole extraction of the counter electrode, leading to a PCE of 11.4%.…”
Section: The Mesoporous Scaffoldmentioning
confidence: 97%
“…PCBM/Al or a carbon electrode is generally employed for electron collection. In a recent report, a layered mesoporous scaffold successively assembling both n-type TiO 2 and p-type NiO has been shown [116]. The device exhibited extended electron lifetime and improved hole extraction of the counter electrode, leading to a PCE of 11.4%.…”
Section: The Mesoporous Scaffoldmentioning
confidence: 97%
“…Another method involves the introduction of interfacial layer between the perovskite and carbon layer. Wang and co-workers [72,83,84] reported the use of NiO as hole selective contact and achieved a PCE of over 15% with the mesoscopic TiO2/Al2O3/NiO/carbon quadruple-layer architecture (Fig. 9d).…”
Section: Pscs With Carbon Electrodementioning
confidence: 99%
“…Recently, significant improvements on NiO-based PSCs were made by doping the NiO thin film or modifying the NiO/perovskite interface heterojunction [98][99][100][101][102]. Kim et al demonstrated a high-efficiency planar PSC by using solution-processed copper (Cu)-doped NiO x (Cu:NiO x ) as a HTM [122].…”
Section: Planar Nio-based P-i-n Pscsmentioning
confidence: 99%
“…The PSCs were composed of FTO/compact TiO 2 /mesoporous TiO 2 /mesoporous NiO/carbon, in which the light absorber CH 3 NH 3 PbI 3 was infiltrated inside the pores of mesoporous TiO 2 /mesoporous NiO/carbon via sequential deposition [101]. Application of mesoporous NiO as a HTM effectively suppresses charge recombination and facilitates hole extraction, resulting in a cell with a PCE of 11.4% [102]. Furthermore, the same groups applied highly-crystalline NiO nanosheets as top nanostructured charge transport layers and inserted an additional mesoporous ZrO 2 layer to achieve an n-i-p heterojunction.…”
Section: Mesoporous Nio-based N-i-p Pscsmentioning
confidence: 99%